SUPERLATIVE ADJECTIVES OF KANGEAN DIALECT OF MADURESE LANGUAGE: A PRAGMATIC STUDY (ADJEKTIVA SUPERLATIF BAHASA MADURA DIALEK KANGEAN: SEBUAH KAJIAN PRAGMATIK) - Muta'allim Muta'allim; Akhmad Sofyan; Akhmad Haryono (UIN Raden Mas Said Surakarta, 2020)
Superlative adjectives of Madura Kangean Dialect (MKD) are Â repetitive adjectives that has R+D+(-an) structure or paleng. Superlative adjectives in MKD are used to describe different functions of utterances according to the contexts. The native people of Kangean island possess a distinctive dialect called Kangean dialect. This study explored the functions of superlative adjectives in MDK. Theories used to determine the functions of superlative adjectives in this research are descriptive and pragmatic theory. This study employed participatory observation method. The data were obtained from interviews with the dialect speakers by voice recording and field note -taking. In addition, the researchers also used reflective-introspective method. The collected data were then transcribed into written form of orthographic transcription. The method applied for analyzing the data are equivalent and distributional method. Meanwhile, the methods used for displaying the results of data analysis are informal and formal steps. The results of this study indicate that superlative adjectives of MKD have different functions, such as for giving motivation, praise, reprimand, satire, advice, orders, blemishes and accusations.